Mineral development for growth: developing a mineral policy framework and mining cadastre system for Pakistan - Ashraf, Hamid (My University, 2017)
Mineral resources can act as key for economic growth and have the potential to transform economies and societies. The extent to which such transformation takes place varies depending upon the method of their use. Pakistan is gifted with significant mineral resources that have the potential to lift its economy and bring prosperity to its citizens. For this to happen, Pakistan must formulate a mineral policy based on leading practices to attract mining investment and increase the sector contribution to GDP in the range of 3 – 5%. The fundamental objective of this research is to investigate the process of mineral policy development of Pakistan against leading developing minerals-based economies and to formulate a strategic fit mineral policy framework, keeping in mind its fragile political, socio-economic and security environment. Developing countries with mineral wealth must try to gain maximum benefit from their mineral resources. These are national assets and should be managed responsibly and not used unwisely. For the gap analysis between Pakistan‘s current mineral policy framework and leading developing countries, five criteria were formulated. Two basic principles were kept in mind with the choice of countries; first, a developing country like Pakistan should be selected; and second, at least two countries should be Islamic. Eight developing courtiers, Chile, Mexico, Brazil, Peru, India, South Africa, Kazakhstan and Turkey were selected for analysis. The key elements for the mineral sector of Pakistan are; Pakistan‘s mineral sector is lacking an enabling institutional framework for efficient access to mineral resources; it lacks an enabling fiscal and regulatory framework for mining to enhance the economic attractiveness of the sector; and the absence of a mining Cadastre System to secure mineral rights prevents security of tenure. Six stakeholders, Government and its implementation bodies; Mining industry; Local communities and their representatives; Law enforcing agencies (LEA's); Religious Monarchs; and Financial institutions were identified and their role defined in policy development framework. A new mineral Policy Framework was formulated based on seven key enablers, namely; institutional framework; stable political economy; legal framework; regulatory framework; fiscal framework; stakeholder participation; and sustainable development. A new organisational structure of the Ministry is proposed based on the generally accepted organisational structure of tiers, implementation and regulatory bodies. An implementation plan based on three building blocks was developed for implementation of the new Mineral Policy Framework. Implementation of an enabling Institutional framework and other key elements of mineral policy framework were suggested to be implemented through the constitution of a Mineral Development Advisory Committee (MDAC). A PakMining Cadastre system was suggested to be constituted under the new Ministry for secure minerals rights system. System design and the geometrical architecture of the PakMining Cadastre System were also suggested.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2017
Keywords: Mines and mineral resources--Government policy--Pakistan; Mines and mineral resources--Planning; Cadastres--Pakistan; Pakistan--Politics and government